PEMBUATAN PURWARUPA DATA WAREHOUSE AKTIFITAS MATERIAL UNTUK MENDUKUNG SISTEM MANAJEMEN INVENTORI DI PT CALTEX PACIFIC INDONESIA - Untung B Santoso; Arif Djunaidy (Lembaga Penelitian dan Pengabdian kepada Masyarakat- Institut Teknologi Sepuluh Nopember, 2005)
In early 2004, PT Caltex Pacific Indonesia (PT CPI) booked US 100 millions for its material inventory level. As one of the company’s Key Performance Indicators (KPI), management recommended to reduce this material inventory level to fit with the current condition of the company. By the end of 2004, company recorded US 82 millions for its material inventory level while the target was US 75 millions. In order to help company to achieve this target, there is a need to provide an additional tool to support the decision making process related to inventory management.This research was focused on the design and implementation of analysis tool (i.e. a prototype of data warehouse for material activity) to support inventory management system at PT CPI. The strategy used in this research was done effectively and efficiently without sacrificing customer’s satisfaction due to the limitation of the resources (i.e. manpower and cost) provided by the company. In the design phase, a dimensional modelling was employed by optimizing some features in SQL Server 2000 to complement the current needs on query and reporting information for inventory analysis that can not be accommodated by the existing JDE Enterprise Resource Planning (ERP). A data cube was created using the star-schema dimensional modelling. This cube enables user to directly perform the slice and dice, as well as drill-down operation easily. In addition, users can also access the cube from Microsoft Excel and web using the Pivot Table Services. The prototype that has been successfully developed in this research has been successfully tested using material activity data during the year 2004 and during a few months in year 2005.In conclusion, the methodology adopted in this research is particularly effective and efficient for developing a data warehouse that uses SQL Server 2000 as a database management system. The prototype developed in this research can be used as a supporting tool for decision making process, in this regard, users will be able to manage material inventory in a better and faster way, which will in turn improve the company’s performance.